2009
DOI: 10.1007/s00540-009-0746-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of ryanodine receptor type 1 p.R2508C mutation in exon 47

Abstract: We demonstrated that the transfected RYR1 mutant was more sensitive to caffeine and 4CmC than wildtype RYR1. These findings suggest that the p.R2508C mutation may be pathogenetic for susceptibility to MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…His mother, patient number 18, had no identifiable mutations in RYR1 20 . The clinical presentation of patient number 2, suspected myopathy, had been reported previously 21 .…”
Section: Patientsmentioning
confidence: 88%
See 2 more Smart Citations
“…His mother, patient number 18, had no identifiable mutations in RYR1 20 . The clinical presentation of patient number 2, suspected myopathy, had been reported previously 21 .…”
Section: Patientsmentioning
confidence: 88%
“…Not all RYR1 mutations cause MH, and several studies have shown that some RYR1 mutations are actually hyposensitive to RYR1 activators 29,30 . We did not perform a genetic analysis on all of the patients enrolled in this study, but three of the study subjects had undergone RYR1 analysis as part of earlier studies 20,21 . Patient number 18, the parent of an individual with a documented episode of MH, carried no mutations of RYR1, but two causative mutations (p.L4838V and p.R2508C) were identified in patients number 1 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the muscle contracture test can be confounded by many factors, including gender and size of muscle preparations [Robinson et al., ]. In contrast, heterologous expression systems of RYR1 in HEK293 cells [Tong et al., ; Wehner et al., ; Monnier et al., ; Migita et al., ] is well‐suited to evaluate effects of RYR1 mutations themselves on channel function because this system is free from background of individual patients. In the course of this and previous works [Murayama, ], we noticed the following important differences in Ca 2+ homeostasis between HEK293 cell systems and skeletal muscles or myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…Over 300 RyR mutations have been associated with disorders (54), including the RyR myopathies malignant hyperthermia (69,72), central core disease (63), multiminicore disease (25), atypical periodic paralyses (125), catecholaminergic polymorphic ventricular tachycardia, and arrhythmogenic right ventricular dysplasia type 2 (64,87,120). The RyR has also been indirectly linked to acquired pathologies such as heart failure (95) and over-exercise muscle fatigue (4).…”
Section: Ryr-associated Pathologiesmentioning
confidence: 99%